Inventing Antillean Narrative: Maryse Condé and Literary Tradition - Leah D. Hewitt (Studies in 20th & 21st Century Literature, 1993)
As a Guadeloupean black woman novelist, Maryse Condé highlights the tensions in Caribbean culture between traditional and modern values, among ethnic groups, and between the sexes. She combines a representative view of an Antillean writer's specific concerns with a postmodern view of literature as multicultural, polymorphous intersection. The opening portion of this essay argues that Condé's personal literary trajectory embodies a general process of identity formation in post colonial literature, one that passes from the alienation of the individual, to the affirmation of collective movements and positive models, and finally, to a critical, playful outlook in which identities are continually posited, criticized and complicated. In the last section, a reading of Condé's recent novel, Traversée de la mangrove, analyzes how the author self-consciously plays on the properties of the novel, much in the way French New Novelists have done. But Condé's work also underscores the importance of references to a given culture, a historical moment. Typical of her generation, Condé's relaxes the barriers between the New Novel's self-consciousness and a social referentiality that stresses the interaction between literature and culture. Concurrently, her reading of gender refuses absolute difference, while nevertheless tracing social inequalities that cause a black woman's plight to exceed her brother's.
Keywords: Guadeloupean black woman novelist; Maryse Condé; Guadeloupean; black; woman; Caribbean culture; traditional; modern values; ethnic groups; sexes; gender; Antillean writer; postmodern; multicultural; polymorphous; Condé; identity; post colonial; Traversée de la mangrove; literature; culture; difference; social inequalities; black woman